Virulent coliphages in 1-year-old children fecal samples are fewer, but more infectious than temperate coliphages - Aurélie Mathieu (Nature Portfolio, 2020)
The impact of bacteriophages in the human gut microbiome remains poorly understood. Here, the authors characterize coliphages isolated from a large cohort of 1-year-old infants and show that temperate coliphages dominate, while virulent ones have greater infectivity and broader host range.